Hitler : beyond evil and tyranny - Stolfi, Russel H. S. 1932- (Prometheus Books, 2011)
The author reinterprets the known facts about the Nazi fuehrer to construct a convincing, realistic portrait of the man. In place of the hollow shell whom others have made into an icon of evil, Stolfi sees a complex, nuanced personality. He tells the story of Hitler, starting with the dreamy youth who showed talent for architectural design but who struggled academically and floundered without direction. The authoe ranks Hitler's successes from 1919 through 1941 as achievements so astonishing that he must be characterized, along with Alexander the Great, Julius Caesar, and Napoleon, as one of Hegel's impossibly rare world historical personalities. This revision of Hitler biography brings us closer to understanding a pivotal personality in the history of mankind